Consequences of technology and social innovation on traditional business model - Vrontis, Demetris; Morea, Donato; Basile, Gianpaolo; Bonacci, Isabella; Mazzitelli, Andrea (Technological Forecasting and Social Change, 2021)
The growing presence of new players – beside those belonging to the institutional and third sectors – committed to supporting social and environmental causes through innovative approaches and tools leads to the profile of a for-profit enterprise increasingly committed to the pursuit of social goals. In the paper, the authors focus their attention on the existence of relationships between innovation and a company's social role in order to assess how innovation affects the social conduct of profit-making enterprises and to determine the birth of a new "hybrid" business model. In order to achieve this goal, research was carried out on a sample of 4,000 Italian Small and Medium-sized Enterprises that claim to operate according to a corporate social commitment, in order to investigate the existence of a relationship between innovative behavior and social and business purposes of companies having different Corporate Social Innovation policies. The data were analyzed using the conditional inference tree, a non-parametric class of tree regression model, which overcomes different regression problems involving ordinal and nominal variables. The results achieved make it possible to fill some gaps in the existing literature, to detect a relationship between technological and social commitment in a company and to open a debate on future research developments.
Keywords: Responsabilité sociétale des entreprises; Réservé UdeM; Social business model